A pragmatic, multi-centered, stepped wedge, cluster randomized controlled trial pilot of the clinical and cost effectiveness of a complex Stroke Oral healthCare intervention pLan Evaluation II (SOCLE II) compared with usual oral healthcare in stroke wards. Issue 3 (April 2020) - Brady, Marian C; Stott, David J; Weir, Christopher J; Chalmers, Campbell; Sweeney, Petrina; Barr, John; Pollock, Alex; Bowers, Naomi; Gray, Heather; Bain, Brenda Jean; Collins, Marissa; Keerie, Catriona; et al.
Background: Patients with stroke-associated pneumonia experience poorer outcomes (increased hospital stays, costs, discharge dependency, and risk of death). High-quality, organized oral healthcare may reduce the incidence of stroke-associated pneumonia and improve oral health and quality of life. Aims: We piloted a pragmatic, stepped-wedge, cluster randomized controlled trial of clinical and cost effectiveness of enhanced versus usual oral healthcare for people in stroke rehabilitation settings. Methods: Scottish stroke rehabilitation wards were randomly allocated to stepped time-points for conversion from usual to enhanced oral healthcare. All admissions and nursing staff were eligible for inclusion. We piloted the viability of randomization, intervention, data collection, record linkage procedures, our sample size, screening, and recruitment estimates. The stepped-wedge trial design prevented full blinding of outcome assessors and staff. Predetermined criteria for progression included the validity of enhanced oral healthcare intervention (training, oral healthcare protocol, assessment, equipment), data collection, and stroke-associated pneumonia event rate and relationship between stroke-associated pneumonia and plaque. Results: We screened 1548/2613 (59%) admissions to four wards, recruiting n = 325 patients and n = 112 nurses. We observed marked between-site diversity in admissions, recruitment populations, stroke-associated pneumonia events (0% to 21%), training, and resource use. No adverse events were reported. Oral healthcare documentation was poor. We found no evidence of a difference in stroke-associated pneumonia between enhanced versus usual oral healthcare ( P = 0.62, odds ratio = 0.61, confidence interval: 0.08 to 4.42). Conclusions: Our stepped-wedge cluster randomized control trial accommodated between-site diversity. The stroke-associated pneumonia event rate did not meet our predetermined progression criteria. We did not meet our predefined progression criteria including the SAP event rate and consequently were unable to establish whether there is a relationship between SAP and plaque. A wide confidence interval did not exclude the possibility that enhanced oral healthcare may result in a benefit or detrimental effect. Trial Registration: NCT01954212.